Kurikulum Merdeka: Kebijakan dan Strategi Implementasi di MA MBS Jetis Ponorogo - Awwalin, Nabila; Valentin, Nio Nilasari Nur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Curriculum changes aim to make students superior, intelligent and ready to face technological modernization in the future. The Independent Learning Policy is the latest breakthrough established by the Ministry of Education and Culture of the Republic of Indonesia, considering the low quality of education in Indonesia as per the data collected, that Indonesia is still ranked sixth from the bottom when viewed from the 79 countries that master mathematics and literacy. So, to get output that is in accordance with the goals of the Independent Curriculum, there must be implementation of the right strategy, namely 1) Actively implementing Independent Curriculum Planning Training. 2) Carrying out training on the main material of the Merdeka Curriculum. The main material in question is about the content or main aspects of the curriculum 3) Forming a development team 4) Implementing the Merdeka Curriculum in stages 5) Periodic reflection on educational units 6) Facilitating the establishment of a learning community at the unit level Education 7) Bribery Implementation of the Project for Strengthening the Profile of Pancasila Students.